ТЕРМОГАЛЬВАНИЧНІ ЕФЕКТИ У НЕІЗОТЕРМІЧНОМУ ЕЛЕМЕНТІ НА ОСНОВІ ЗАЛІЗО-КАРБОНОВОГО КОМПОЗИЦІЙНОГО ЕЛЕКТРОДУ ТА ЛУЖНОГО ЕЛЕКТРОЛІТУ - Boichuk, Oleksandr; Pershina, Katherine; Riabokin, Oleh; Kravchenko, Alexandr; Panteleimonov, Radyslav (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
In article was established the conditions for measuring thermal diffusion and thermoelectric effects in non-isothermal elements with composite electrodes of powdered iron and carbon in the alkaline electrolytes using electrochemical impedance spectroscopy. By the modeling of the impedance spectra of these systems has been established the most advantageous equivalent model scheme, which confirms that the external resistance has several components: the resistance of the electrolyte, the resistance of the capacity of the double electric layer and the resistance of thermal diffusion, which forms the dispersion of the capacity. By the calculations of the capacity and the dispersion of the capacity in the low- and high-frequency measurement range have been shown the effect of the concentration of composition components on the formation of the additional heat capacity, which creates the preconditions for realizing of the thermal electrical effects. Increasing of a concentration of the iron leads to the increase of the number of oxide (semiconductor) structures that increase the additional heat capacity. Such heat capacity induces electrical capacity and its dispersion. That is, it creates the preconditions for the occurrence of thermoelectric effects, especially Sore effects in the non-isothermal element. This work was realized due the projects of the Purpose Program for Basic Research of the Chemistry Department of NAS of Ukraine "Basic Research in Priority Areas of Chemistry" P - 1 - 17 DR 0117U000856 and "Strategy of creation of new heat-energy systems based on iron and its compounds, sulfur and oxygen" No. 0117U0008.